Influences of Holes Arrangement on Creep Characteristic of Nickel-Base Single Crystal Alloy Blade Cooling Holes - Lei Li; Liangbo Ao; Gongnan Xie; Xinmei Wang; Gang Cao (Advances in Materials Science and Engineering)
Film cooling technology is developed to enhance the temperature resistant of nickel-base single crystal alloy blade. The shape, dimension, and arrangement of cooling holes impact the blade strength and life grievously. In this paper, the influences of holes arrangement on creep characteristic of cooling holes in the plate sample are investigated. The constitutive model for creep considering both cavitation and degradation damage is developed to predict the creep behavior of cooling holes. Results show that there are stress interferences among cooling holes. The distance and radius of the cooling holes impact the creep behavior of cooling holes seriously. Decreasing horizontal distance of the holes results in creep time reducing. On the contrary, increasing the vertical distance of the holes makes the creep time reduced.